Multivariable time-dependent analysis of the impact of azacitidine in patients with lower-risk myelodysplastic syndrome and unfavorable specific lower-risk score. Issue 1 (January 2015) - Falantes, Jose; Delgado, Regina García; Calderón-Cabrera, Cristina; Márquez-Malaver, Francisco J.; Valcarcel, David; de Miguel, Dunia; Bailén, Alicia; Bargay, Joan; Bernal, Teresa; González-Porras, Jose R.; Tormo, Mar; Ramos, Fernando; et al.
Highlights Two scores identify lower-risk patients with survival similar to high-risk patients. Achieving response to azacitidine in these patients appears to impact on survival. Thrombocytopenia is the most important prognostic parameter in lower-risk MDS. This analysis supports a prospective intervention in these poor risk patients.